Perbedaan Pendapatan dan Faktor – Faktor yang Mempengaruhi Adopsi “SRI” di Kecamatan Bojongsoang Kabupaten Bandung - Anjar Hilman Wiguna; Ahyar Ismail; Meti Ekayani (Jurnal Manajemen Pembangunan Daerah, 2025)
ABSTRACT Rice monoculture farming in using fertilizers and inorganic pesticide as the effect of green revolution potentially to be environment problem. One of the friendly environtment farming as the solution is System of Rice Intensification (SRI). The aim of the research is to analyze differences farmer’s income who applying SRI and conventional way, identify adoption level of SRI and influential adoption factors. The result shows average SRI farmer’s income is twice higher from the conventional with 1,59 ;1,35 R/C ratio. Higher production and selling price impacts higher SRI farmer’s income. There are 70,83% from all over respondent know the SRI and the rest (29,17%) don’t know about the SRI. But some who know doesn’t apply it because by it’s high production cost, in this case is organic fertilizers. Adoption level of using organic fertilizers component is in “kadang sesuai anjuran” (KSA) level, but the application of whole SRI component is in “sering sesuai anjuran” (SSA) level. The significant factors in adopting SRI are age, farming experience, education, land area, utilization of agricultural waste, premium price and efficient-water use. Keywords: SRI (System of Rice Intensification), farmer income, level of adoption, the influential factors